STUDIES ON THE PRESERVATION OF FISH BY PICKLING - Subramanya Rao, A P; Valsan, A P; Rajendranathan Nair, M (Indian Journal of Fisheries, 2016)
Pickling with salt, vinegar, sugars and spices forms a traditional methodof food preservation and is also widely employed for fish curing. A greatvariety of fishery products prepared with vinegar and spices enjoy widepopularity in Germany and other north European countries. Pickling isalso practised in the East in countries like China, Japan and the Philippines(Jarvis, 1950). Although pickled products are of a semiperishable naturesince the concentrations of salt and vinegar employed are limited by considerationsof palatability, they possess a greater appeal to consumers thansalted and dried fish. Moreover these methods are better suited for curingfatty fish which are susceptible to rancidity in other salting methods. Apartfrom a few spiced and pickled products Uke PADDA and MOLLEI preparedon a domestic scale from Seer fish, Colombo Cure of the West Coast formsthe chief commercial method in India which employs principles of pickling.Mackerels, Seer and non-fatty sardines are treated by this process and Malpein South Kanara exports considerable quantities of Colombo cured fish toCeylon (Nicholson, 1930). Malabar tamarind or ' Goruka PuU', the driedfleshy pod of Garcinia cambogea is used as an adjunct to salt in order toobtain the desired acidity.